A Fast and Selective Near-Infrared Fluorescent Sensor for Multicolor Imaging of Biological Nitroxyl (HNO) - Wrobel, Alexandra T. (American Chemical Society, 2014)
[Image: see text] The first near-infrared fluorescent turn-on sensor for the detection of nitroxyl (HNO), the one-electron reduced form of nitric oxide (NO), is reported. The new copper-based probe, CuDHX1, contains a dihydroxanthene (DHX) fluorophore and a cyclam derivative as a Cu(II) binding site. Upon reaction with HNO, CuDHX1 displays a five-fold fluorescence turn-on in cuvettes and is selective for HNO over thiols and reactive nitrogen and oxygen species. CuDHX1 can detect exogenously applied HNO in live mammalian cells and in conjunction with the zinc-specific, green-fluorescent sensor ZP1 can perform multicolor/multianalyte microscopic imaging. These studies reveal that HNO treatment elicits an increase in the concentration of intracellular mobile zinc.